Group Schema Therapy for Refugees with Treatment-Resistant PTSD and Personality Pathology - Linda Verhaak; Jackie June ter Heide (Case Reports in Psychiatry)
Introduction. Patients with complex forms of posttraumatic stress disorder (PTSD) may benefit from schema therapy. While a small number of studies point to the effectiveness of individual schema therapy in refugees with PTSD, no evidence on group schema therapy (GST) in refugees exists. To illustrate and advocate for the use of GST in refugee patients with treatment-resistant PTSD and comorbid personality pathology, a case report is presented. Presentation. The case concerned the treatment of an East African female refugee who survived sexual and physical violence and loss as a child, as the hostage of a rebel army, and as a victim of human trafficking. She was diagnosed with PTSD, major depressive disorder, and borderline personality disorder. Trauma-focused therapy was hampered by insufficient treatment attendance due to current stress factors and early destructive coping strategies. One year of GST enabled the patient to overcome treatment-undermining patterns and benefit from subsequent trauma-focused therapy. Conclusion. This case suggests that GST may have the potential to improve treatment adherence and the effectiveness of trauma-focused treatment in complex refugee patients. Clinical impressions need to be confirmed in a study that examines the feasibility, acceptability, and preliminary efficacy of GST in refugees with treatment-resistant PTSD and personality pathology.